The Determinant of The Slaughterhouse Workers’ Work Fatigue at The laughterhouse in Situbondo and Jember - Rayi Siti Nurbaya; Hadi Prayitno; Isa Ma’rufi (Health Notions, 2020)
The factor causing work accident at the slaughterhouse is one of them, work fatigue. Work fatigue is influenced by internal and external factors, such as age, job tenure, sleep quality, and workload. This research aimed to analyze the determinant factor affecting work fatigue suffered by the workers of the slaughterhouse in Situbondo and Jember, such as age, job tenure, sleep quality, and workload. Also, an analysis was carried out to determine the main dominant factor affecting work fatigue of the slaughterhouse workers. The design of the research used analytic observational and cross-sectional research. The population consisted of 51 workers determined by using census sampling technique, in which all the population was used as the samples. The analysis techniques used were logistic regression. The result of the research revealed that there was an effect of age, job tenure, and workload on work fatigue. Meanwhile, no significant effect found in the sleep quality toward work fatigue. Age was the main dominant factor affecting work fatigue. Keywords: age; job tenure; sleep quality; workload; work fatigue